Time Difference Of Arrival Estimation Using Fast Fourier Transform Overlap For Underwater Positioning - Tan, Chee Sheng (2019)
This project presents an underwater acoustic positioning system based on time difference of arrival (TDOA) measurement. In this research, an underwater communication device is developed and fast Fourier transform (FFT) overlap algorithm is proposed in order to achieve the objectives. The TDOA technique is used to estimate the position of an underwater target. The TDOA estimation is derived based on the intensity of a received signal with the frequency of interest. An extraction of a signal from a receiver is performed by using digital signal processing algorithms. The FFT is used to convert the receiving signal from time domain into frequency domain for extraction of the signal information (relevant frequency and amplitude). Hence, the TDOA estimation can be obtained from the frequency information using an overlap transform processing. Experimental results are presented to demonstrate the capabilities of the proposed algorithms. The results indicate that the proposed FFT with 100% overlap has successfully improved an accuracy with percentage error of 1.71% for the TDOA estimation. Overall, the positioning system using FFT overlap able to provide an accurate positioning estimation.